2018
DOI: 10.1111/pce.13422
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycle acceleration and changes in essential nuclear functions induced by simulated microgravity in a synchronized Arabidopsis cell culture

Abstract: Zero gravity is an environmental challenge unknown to organisms throughout evolution on Earth. Nevertheless, plants are sensitive to altered gravity, as exemplified by changes in meristematic cell proliferation and growth. We found that synchronized Arabidopsis-cultured cells exposed to simulated microgravity showed a shortened cell cycle, caused by a shorter G2/M phase and a slightly longer G1 phase. The analysis of selected marker genes and proteins by quantitative polymerase chain reaction and flow cytometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 82 publications
(127 reference statements)
2
22
0
Order By: Relevance
“…In contrast with the downregulation of phototropism and related biosynthetic and metabolic pathways, we found two very clearly upregulated functions in microgravity‐grown seedlings when compared to 1‐ g spaceflight samples: ribosome biosynthesis and oxidative phosphorylation (Appendices S16 and S17). In both true microgravity (Matía et al., ) and different simulated microgravity facilities using both seedlings and cell cultures (Manzano et al., ; Kamal et al., ), ribosome biogenesis was reduced. Our recent spaceflight results showed that red light can compensate for this effect (Valbuena et al., ), particularly by increasing cell growth (measured by means of ribosome biosynthesis in the nucleolus) that was depleted without light stimulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast with the downregulation of phototropism and related biosynthetic and metabolic pathways, we found two very clearly upregulated functions in microgravity‐grown seedlings when compared to 1‐ g spaceflight samples: ribosome biosynthesis and oxidative phosphorylation (Appendices S16 and S17). In both true microgravity (Matía et al., ) and different simulated microgravity facilities using both seedlings and cell cultures (Manzano et al., ; Kamal et al., ), ribosome biogenesis was reduced. Our recent spaceflight results showed that red light can compensate for this effect (Valbuena et al., ), particularly by increasing cell growth (measured by means of ribosome biosynthesis in the nucleolus) that was depleted without light stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of cell growth and cell proliferation, it has been shown that when seedlings are grown in darkness, there is a lack of balance between these key plant development functions in microgravity (Matía et al., ). Further evidence for this observation was provided by analyzing a dark‐grown, synchronized cell culture grown in simulated microgravity (Kamal et al., ). Recent spaceflight results show that red light can compensate for this effect (Valbuena et al., ), particularly increasing cell growth (measured by means of ribosome biosynthesis in the nucleolus) that was depleted without light stimulation.…”
mentioning
confidence: 91%
“…These reference times have been confirmed by flow cytometry in a parallel experiment with aliquots of the same cell culture system and microgravity simulator conditions as described here [28]. Cells were recovered from the agorose and frozen until RNA extraction.…”
Section: Microgravity Simulator and Experimental Designmentioning
confidence: 69%
“…Since we had previously established that there was a quick entry into M phase under simulated microgravity conditions [28], agarose-embedded cultures (synchronous and asynchronous subpopulations) were exposed to simulated microgravity conditions for different experimental durations accordingly. To obtain the maximum enrichment in each cell cycle subpopulation (higher than 2/3 of the cell population), the exposure time was 7h RPM / 10h 1g control hours for the G2/M synchronized samples, 14h RPM / 16h 1g control for the G1 synchronized cells and 14h RPM / 14h 1g control for the asynchronous reference cells.…”
Section: Microgravity Simulator and Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation